Study of the effect of the xenobiotic hormone on the reproductive function of rats - Kononenko, Nadiia; Minukhin, Andrey; Chikitkina, Valentyna (ScienceRise: Medical Science, 2020)
The aim is to study the effect of the xenobiotic of Nonylphenol on functional and morphological indices of the reproductive system of males of rats. Materials and methods. Experimental modelling of gonadotoxic effects of the xenobiotic was performed by inhalation of Nonylphenol at a concentration of 500 mg/m3 for 30 days, 5 days a week, 5 hours a day in conditions of the seed chamber. Male rats ejaculate were obtained by the method of electrostimulation seed tubercle in the mucous membrane of the rectum. The number of sperm in the ejaculate and their mobility were determined in the Hemocytometer 1, 7, 14 and 30 days after the start of the experiment. Macroscopic study of the testes included the assessment of external signs of damage, the determination of the mass and length of the testes. Results. It is established that the introduction of Nonylphenol to rats males leads to a gradual dynamical reduction of the total number and the number of mobile forms of sperm cells compared to intact animals. At the end of the experiment the number of mobile forms of sperm was 2.1 times below the original data. Long-term effect of Nonylphenol has also led to a significant decrease of body weight growth, which confirms its high toxicity. In the study found that intoxication in Mature rats Nonylphenol were significant changes in the reproductive system, which is primarily characterized by decreased weight of the testes and the appendages of the testis, and changes in linear dimensions of the bodies downward. These violations indicate a feminizing effect of this hormone-like xenobiotic and its role in the development of male infertility. Conclusions. Quantitative and qualitative parameters of the ejaculate of sexually mature male rats can serve as a valid criterion for adaptive and maladaptive processes occurring in the organism under the influence of the xenobiotic. In conditions of prolonged exposure to Nonylphenol (within 30 days) the changes in mass of the testes and reduce their linear dimensions